A Review of the Teaching Methods and Techniques - Parvin Samadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the basic functions of the education system is to pay attention to the principles of education, and in this regard, teaching is an art, so teachers need to how to teach with quality. The compilation of the book Teaching Methods and Techniques is one of the scientific endeavors that this research aims to criticize. This study was carried out by the method of critical philosophical exploration in the critique of the mentioned book, compiled by Manouchehr Vakilian, 16th edition, in 2016. The study tool was a review of academic textbooks and reviews of the Humanities Textbook Council. Based on the findings, the benefits of book’s format analysis include cover design, typography, good print, and book quality. The strengths of the content analysis include content fit for the course objectives, good coverage of approved subject headings, and book-level fit. Academic students of Payam-e Noor are partly responsive to scientific and applied needs, paying attention to theoretical foundations and subjective assumptions, observing scientific and ethical principles, and adapting to religious and Islamic principles and principles. Formal and substantive deficiencies in the work include inadequate referral status, weak criticism and analysis, outdated sources, and data.